Improvement of Mechanical, Thermal, and Morphological Properties of Organo-Precipitated Calcium Carbonate Filled LLDPE/Cyclic Natural Rubber Composites - Novesar Jamarun; Syukri Arief; Hermansyah Aziz; Boy Isfa; Ahmad Hafizullah Ritonga; Denny Akbar Tanjung (Indonesian Journal of Chemistry, 2022)
This study investigates the improvement of the mechanical, thermal, and morphological properties of linear low-density polyethylene (LLDPE)/cyclic natural rubber (CNR) after the addition of organo-precipitated calcium carbonate (O-PCC). The impact on the properties of the LLDPE/CNR/LLDPE-g-OA/O-PCC composites was investigated by a series of empirical experiments. First, the polymer composite was blended in the molten state using an internal mixer with a heating temperature of 160 °C and a rotation speed of 100 rpm. The LLDPE was placed in a chamber of internal mixer until melted, followed by CNR, LLDPE-g-OA, and O-PCC. The polymer composites with an O-PCC concentration of 5% obtained the optimal mechanical properties compared to other variations, with a tensile strength of 17.17 MPa and Young's modulus of 252.68 MPa. The presence of O-PCC resulted in better thermal stability and a change in the melting point temperature of 124 °C. The FTIR spectra of the polymer composite showed the specific characteristics of O-PCC at 872.1 cm–1. The morphology of the polymer composite indicates that the O-PCC is evenly dispersed in the polymer composite.